From Sensorimotor Experiences to Cognitive Development: Investigating the Influence of Experiential Diversity on the Development of an Epigenetic Robot - Lones, John; Lewis, Matthew; Cañamero, Lola (Frontiers in Robotics and AI, 2016)
Using an epigenetic model, in this paper we investigate the importance of sensorimotor experiences and environmental conditions in the emergence of more advanced cognitive abilities in an autonomous robot. We let the robot develop in three environments affording very different (physical and social) sensorimotor experiences: a ``normal'', standard environment, with reasonable opportunities for stimulation, a ``novel'' environment that offers many novel experiences, and a ``sensory deprived'' environment where the robot has very few and over-simplistic chances to interact. We then: (a) assess how these different experiences influence and change the robot's ongoing development and behavior; (b) compare the said development to the different sensorimotor stages that infants go through and (c) finally after each ``baby'' robot has had time to develop in its environment, we recreate and asses its cognitive abilities using different well-known tests used with human infants such as violation of expectation (VOE) paradigm. Although our model was not explicitly designed following Piaget's, or any other sensorimotor developmental theory, we observed, and discuss in the paper, that relevant sensorimotor experiences, or the lack of, result in the robot going through unplanned development ``stages'' bearing some similarities to infant development, and could be interpreted in terms of Piaget's theory.